THE INFLUENCING FACTORS OF TOURIST SATISFACTION AND VISITS IN TAMAN SERIBU BUNGA AGROTOURISM - Pakpahan, Helena Tatcher; Simatupang, Donny; Manik, Mitro (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to determine the factors influencing tourist visits during the Covid-19 pandemic. The sampling method was selected purposively at Taman Seribu Bunga Agrotourism County 1, Raya, Berastagi District, Karo Regency, North Sumatra Province. This sampling method uses Purposive Sampling, which is a sampling technique that is not based on random, region or strata but based on considerations that focus on specific goals with a total of 100 respondents. The results showed that the factors influencing visitor satisfaction were: a) Independent variables (infrastructure with a beta coefficient of 0,426 and promotions with a beta coefficient of 0,315) had a positive effect on visitor satisfaction resources (with a beta coefficient of 0,051 and institutions with a beta path coefficient 0,023) simultaneously has a positive but not significant effect on visitor satisfaction. b) The factors that influence tourist visits are: a) Independent variables (infrastructure with a beta coefficient of 0,475, promotion with a beta coefficient of 0,440 and visitor satisfaction with a beta coefficient of 0,554) have a positive and significant effect on tourists visits and resource (coefficients beta line 0,027 and institutional coefficient beta line 0,152) has a positive but not significant effect on tourist visits.